Pembelajaran Seni Rupa 2 Dimensi dengan Menggunakan Media Triplek pada Kelas XII di SMAN 2 Pekanbaru - Ghina Salsabila; Yahyar Erawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to describe the implementation of cultural arts learning (two-dimensional fine arts) in class XII of SMAN 2 Pekanbaru. In this study, researchers used learning theory from E. Mulyasa (2013). This type of research is qualitative. The method used in this research is a qualitative descriptive method, namely observation, interviews and documentation. The author made observations and then interviewed several sources. The author reviews documentation regarding the information data that the author has obtained. This research was conducted at SMAN 2 Pekanbaru. The results of the research show that the implementation of cultural arts (two-dimensional fine arts) learning for class XII at SMAN 2 Pekanbaru is guided by the curriculum, syllabus and lesson plans. The curriculum used by SMAN 2 Pekanbaru in class XII is the 2013 curriculum which is implemented face to face. In preparing learning plans, arts and culture teachers are also guided by the 2013 curriculum which has been determined by the school and the syllabus is determined by the government and then adjusted to school conditions. The learning methods used are lecture, discussion, question and answer and practice methods. The media used when learning Fine Arts are worksheets (students), printed books, and the internet. The tools used by teachers in teaching and learning activities are whiteboards, markers and assessment sheets. The evaluation assessed by the Arts and Culture teacher is the completeness value of the assignment collection, knowledge value, and skills value.